The Xbp1-regulated transcription factor Mist1 restricts antibody secretion by restraining Blimp1 expression in plasma cells - Wöhner, Miriam; Pinter, Theresa; Bönelt, Peter; Hagelkruys, Astrid; Kostanova-Poliakova, Daniela; Stadlmann, Johannes; Konieczny, Stephen F.; Fischer, Maria; Jaritz, Markus; Busslinger, Meinrad (Frontiers in Immunology, 2022)
Antibody secretion by plasma cells provides acute and long-term protection against pathogens. The high secretion potential of plasma cells depends on the unfolded protein response, which is controlled by the transcription factor Xbp1. Here, we analyzed the Xbp1-dependent gene expression program of plasma cells and identified Bhlha15 (Mist1) as the most strongly activated Xbp1 target gene. As Mist1 plays an important role in other secretory cell types, we analyzed in detail the phenotype of Mist1-deficient plasma cells in Cd23-Cre Bhlha15fl/fl mice under steady-state condition or upon NP-KLH immunization. Under both conditions, Mist1-deficient plasma cells were 1.4-fold reduced in number and exhibited increased IgM production and antibody secretion compared to control plasma cells. At the molecular level, Mist1 regulated a largely different set of target genes compared to Xbp1. Notably, expression of the Blimp1 protein, which is known to activate immunoglobulin gene expression and to contribute to antibody secretion, was 1.3-fold upregulated in Mist1-deficient plasma cells, which led to a moderate downregulation of most Blimp1-repressed target genes in the absence of Mist1. Importantly, a 2-fold reduction of Blimp1 (Prdm1) expression was sufficient to restore the cell number and antibody expression of plasma cells in Prdm1Gfp/+ Cd23-Cre Bhlha15fl/fl mice to the same level seen in control mice. Together, these data indicate that Mist1 restricts antibody secretion by restraining Blimp1 expression, which likely contributes to the viability of plasma cells.